The effectiveness of the implementation of deep breaths on psychosocial problems in the family during the pandemic - Heni Nurhaeni; Dinarti Dinarti; Mega Khoirunnisa (Politeknik Kesehatan Kemenkes RI Jakarta I, 2021)
Background: Outcome expectancy could mediate the psychological effects of exercise-related interventions, which implies that part of the psychological benefits of physical activity could be ascribed to placebo effects. (Szabo & Kocsis, 2017) Purpose: Knowing the effects of relaxation breathing on Anxiety in patients with psychosocial problems in the family during the pandemic Methods: The type of research used is quantitative quasi experimental, non-equivalent, control group pretest and posttest design. The population in this study was some family members who have anxiety problem with the sample of 39 respondents. Samples were taken using purposive sampling technique. Results: The average levels a score before 61,08% and after 60,82% deep breath of relaxation with p value = 0.043 (<0.05). It can be concluded that deep breathing relaxation techniques has effects on the reduction of anxiety in some of family member Conclusion: Deep breathing relaxation techniques can reduce reduction in effects on the reduction in some of family member. Recommendation to reduce management to be applied a deep breathing relaxation techniques as standard of operational procedures (SOP) in the context of nursing care, especially to effects on the reduction in some of family member especially at pandemic